The Implementation of Psychoreligious Therapy to Overcome Drug Addiction in Santri in At-Tauhid Islamic Boarding School Semarang - Fikha, Rizky Ardlillahtul; Seedat, Mohamed (Journal of Sufism and Psychotherapy, 2023)
Drugs are one of the problems currently being faced by Indonesia. Drugs have a negative impact on the abuser both physically, psychologically and spiritually. The purpose of this research is to find out the implementation of psychoreligious therapy in dealing with drug addiction among Islamic students at the At-Tauhid Islamic Boarding School, Semarang. This study uses a qualitative approach with a type of field research research. Data collection is done by observation, interviews and documentation. By using the data analysis techniques of the Miles and Huberman model. In this analysis, there are several steps including: the data collection stage, the data reduction stage, the data presentation stage, and the conclusion stage. The results of this study indicate that the condition of a drug addict has changed after applying Psychoreligious Therapy both physically, psychologically and spiritually for students who are addicted to drugs. The methods or methods applied in Psychoreligious Therapy at the At-Tauhid Islamic Boarding School in Semarang include: dhikr, congregational prayers, bathing in repentance, fasting and prayer.